REKONSTRUKSI HUKUM PERKAWINAN BEDA AGAMA PRESPEKTIF HAK ASASI MANUSIA - Ibnudin, Ibnudin; Mursyid, Ali (Moderation | Journal of Islamic Studies Review, 2024)
The development of cases of interfaith marriage in Indonesia is increasing, while Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage is still not clearly and firmly regulated, unlike mixed marriages of different nationalities regulated in article 57 of Law number 1 of 1974. Various research results show that interfaith marriage continues to occur in various forms of practice in Indonesia by taking advantage of legal loopholes and diversity of interpretations of the conditions for the validity of marriage according to religious law as stipulated in article 2 paragraph (1) of the Marriage Law No. 1 of 1974. Such an arrangement has the potential to continue a long debate that never ends throughout the political dynamics of marriage law in Indonesia. This article was written in order to study and become a legal offer regarding the issue of interfaith marriage from the perspective of Human Rights (HAM) that guarantees legal certainty, namely the fulfillment of moral rights and legal rights that uphold human dignity based on Pancasila and the Constitution of the State of Indonesia which can then be used as a solution and legal offer.